A model for professional counselors to integrate multiculturalism and social justice into correctional settings. Issue 1 (8th March 2022) - Rio, Jennifer L.; Laux, John M.; Clark, Madeline; Walker, Tanesha; Goodlin‐Fahncke, Wendi; Heckman, Lindsay; DelRe, Jessica
Abstract: The purpose of this study was to develop a theoretical model for how counselors integrate multicultural and social justice competency into their work with persons who have offended. A qualitative grounded theory tradition was used to generate an inductive theoretical model for integrating the Multicultural and Social Justice Counseling Competencies (MSJCC) into correctional settings. Participants ( n = 16) were professional counselors recruited through counseling listservs and snowball sampling who work in prison, residential, jail, private practice, and community mental health settings. The findings revealed the need for ongoing training, multicultural and social justice awareness, and knowledge about structural barriers and systemic oppression.